A membrane electrode cathode catalyst layer and its preparation method and application
By using specific medium-long branched ionomers in the cathode catalytic layer of the membrane electrode and controlling the dispersion pressure of the second catalyst slurry, the problem of perforation or degradation of the membrane electrode catalytic layer is solved during use, and the effect of improving the performance and durability of the membrane electrode is achieved.
Patent Information
- Application Number
- CN202311576677.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-24
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-11-24
AI Technical Summary
The cathode catalytic layer of the existing membrane electrode is prone to perforation or degradation acceleration during use, affecting the life of the membrane electrode.
A medium-long branched ionomer with a side chain carbon atom number of 3-7 and an equivalent molecular weight (EW) of 700-1100 is used as the ionomer of the first catalytic layer to prevent cracking and falling off of the first catalytic layer, and controllable cracking of the second catalytic layer is achieved by controlling the dispersion pressure of the second catalyst slurry.
The integrity of the first catalytic layer is ensured, the controllable cracking of the second catalytic layer is achieved, and the performance of the membrane electrode is improved without affecting its durability.
Smart Images

Figure CN117525444B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a membrane electrode cathode catalyst layer and a preparation method and application thereof. Background Art
[0002] As the core component of fuel cells, the performance and durability of membrane electrode are affected by the structure of the catalyst layer in the catalyst coated membrane (CCM). The usual CCM is divided into three layers, that is, the proton exchange membrane is located in the middle, and the two sides of the proton exchange membrane are the anode catalyst layer and the cathode catalyst layer; the anode catalyst layer is the place where the hydrogen oxidation reaction (HOR) is completed, and the cathode catalyst layer is the place where the oxygen reduction reaction (ORR) is completed; the electrons generated by the anode flow to the cathode after doing work through the external circuit, and the [H+] generated at the same time passes through the electrolyte membrane to reach the cathode, and then reacts with oxygen to produce water.
[0003] The cathode ORR reaction of the membrane electrode is a key step affecting the performance of the fuel cell. 2 When improving the utilization of catalyst reaction sites, it is the key to improve the performance of membrane electrode. For example, the cracked catalyst layer disclosed in patent CN111484410A and the grooved catalyst layer recorded in Grooved electrodes for high-power-density fuel cells can improve the performance of membrane electrode. Although the design of cracks and grooves is conducive to introducing pores and increasing the specific surface area, thereby increasing the utilization of active sites, the above-mentioned through-type cracks will cause part of the membrane electrode proton membrane to be exposed, so that local pressure is formed at the cracks during the operation of the fuel cell, which makes the membrane electrode prone to perforation or accelerated degradation at the cracks, thereby affecting the life of the membrane electrode.
[0004] In response to the above-mentioned problems existing in the use of the membrane electrode, finding a method that can achieve controllable cracking of the second catalytic layer in the membrane electrode while keeping the first catalytic layer intact; and a cathode catalytic layer that improves the performance of the membrane electrode without affecting its durability is the current research focus in the fuel cell field. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a membrane electrode cathode catalyst layer and its preparation method and application; the membrane electrode cathode catalyst layer can achieve controllable cracking of the second catalyst layer and ensure the integrity of the first catalyst layer, while improving the performance of the membrane electrode without affecting the durability of the membrane electrode.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In the first aspect, the present invention provides a membrane electrode cathode catalyst layer, which comprises a first catalyst layer and a second catalyst layer stacked in sequence; the first catalyst layer comprises a first catalyst and a first ionomer, and the second catalyst layer comprises a second catalyst and a second ionomer; the number of carbon atoms in the side chain of the first ionomer is 3-7, and the equivalent molecular weight (EW) is 700-1100.
[0008] The catalytic layer described in the prior art is usually designed with cracks or grooves, which will lead to partial exposure of the proton membrane of the membrane electrode, seriously affecting the life of the membrane electrode.
[0009] In view of the above problems, the present invention adopts a medium- and long-chain branched polymer with a side chain carbon atom number of 3-7 and an EW of 700-1100 as the polymer of the first catalytic layer. This can prevent the solvent in the slurry from penetrating into the first catalytic layer during the process of coating the slurry on the surface of the first catalytic layer, causing the first catalytic layer to crack and fall off.
[0010] The inventors have discovered through a large number of experiments that the use of the above-mentioned specific first ionomer can achieve controllable cracking of the second catalytic layer of the membrane electrode cathode catalytic layer, while ensuring that the first catalytic layer is intact; if a short-chain branched ionomer is used as the first ionomer, due to the large swelling rate of the short-chain branched ionomer, it is easy to change its volume after contacting water or alcohol solvents, thereby causing cracking or deformation, and the integrity of the first catalytic layer cannot be guaranteed. If the number of branched carbon atoms is too large, it will also affect the flexibility of the ionomer, increasing the difficulty of preparing the catalytic layer.
[0011] As a preferred embodiment of the membrane electrode cathode catalyst layer of the present invention, the first catalyst layer is a catalyst layer close to the proton exchange membrane in the membrane electrode.
[0012] As a preferred embodiment of the membrane electrode cathode catalyst layer of the present invention, the second ionomer and the first ionomer can be the same ionomer or different ionomers.
[0013] As a more preferred embodiment of the membrane electrode cathode catalyst layer of the present invention, the second ionomer is a perfluorosulfonic acid resin.
[0014] As a preferred embodiment of the membrane electrode cathode catalyst layer of the present invention, the first catalyst is a Pt / C or Pt-M / C catalyst with a metal content of 10-80wt%; the second catalyst is a Pt / C or Pt-M / C catalyst with a metal content of 10-80wt%; wherein M is at least one of Co, Ni, Mn, Pd, Sn, Au, Ag, Ir, Ru, Cu, and Fe.
[0015] As a more preferred embodiment of the membrane electrode cathode catalyst layer of the present invention, the metal content of the first catalyst is 25-60wt%; the metal content of the second catalyst is 25-60wt%.
[0016] As a preferred embodiment of the membrane electrode cathode catalyst layer of the present invention, the thickness of the first catalyst layer is 0.5-15 μm, and the platinum loading is 0.05-0.3 mg / cm 2 The inventors found through a large number of experiments that if the thickness of the first catalytic layer is >15 μm or the platinum loading is >0.3 mg / cm 2 When the first catalytic layer is less than 0.5 μm or the platinum loading is less than 0.5 μm, the first catalytic layer will be cracked or the first catalytic layer will be damaged when the second catalytic layer is coated, making it incomplete. <O.05mg / cm 2 When the platinum loading is too low and the thickness is too thin, the electrochemical surface area of the catalyst layer is small and the reaction active sites are few, which reduces the performance of the final membrane electrode cathode catalyst layer.
[0017] As a preferred embodiment of the membrane electrode cathode catalyst layer of the present invention, the thickness of the second catalyst layer is 0.5-10 μm, and the platinum loading is 0.05-0.3 mg / cm 2 The inventors found through a large number of experiments that if the thickness of the second catalytic layer is >10 μm or the platinum loading is >0.3 mg / cm 2 If the thickness of the second catalytic layer is less than 0.5 μm or the platinum loading is less than 0.05 mg / cm, the solvent in the second catalytic layer slurry is too much, resulting in a longer evaporation time of the solvent during coating of the second catalytic layer, which may easily cause cracking of the first catalytic layer. 2 When the coating of the second catalyst layer is uneven, wire drawing will occur, which will affect the performance of the cathode catalyst layer of the membrane electrode.
[0018] As a preferred embodiment of the membrane electrode cathode catalyst layer of the present invention, the mass of the first ionomer is 20-45% of the mass of the first catalyst layer; the mass of the second ionomer is 20-45% of the mass of the second catalyst layer; the inventors have found through a large number of experiments that if the content of the ionomer is too low, some active components on the catalyst will not have a catalytic effect due to the lack of contact with the electrolyte. At the same time, the degree of continuous proton transfer channels formed inside the catalyst layer is low, and the proton transfer resistance increases; if the content of the ionomer is too high, the pores of the catalyst layer will become smaller, which is not conducive to the transfer of the reaction gas to the active sites through the pores, causing the electronic resistance to increase, and due to the excessive amount of ionomer, the hydrophilicity of the catalyst layer increases, causing cathode flooding; after optimization, the membrane electrode cathode catalyst layer prepared with the ionomer content within the above range can effectively ensure the balance of electron transfer, proton transfer and material transfer in the catalyst layer, thereby improving the performance of the battery.
[0019] In a second aspect, the present invention provides a method for preparing a membrane electrode cathode catalyst layer as described in the first aspect, comprising the following steps:
[0020] S1, mixing and dispersing a first catalyst, a first solvent and a first ionomer to obtain a first catalyst slurry;
[0021] S2, mixing and dispersing the second catalyst, the second solvent and the second ionomer to obtain a second catalyst slurry;
[0022] S3, applying the first catalyst slurry in step S1 and the second catalyst slurry in step S2 on the proton exchange membrane in sequence, and drying to obtain a membrane electrode cathode catalyst layer.
[0023] As a preferred embodiment of the method for preparing a membrane electrode cathode catalyst layer of the present invention, in step S1, the first solvent is a mixed solution of alcohol and water.
[0024] As a more preferred embodiment of the method for preparing the cathode catalyst layer of the membrane electrode according to the present invention, the alcohol content in the first solvent is 5-30wt%; the inventors have found through a large number of experiments that when the alcohol content in the first solvent is too low, it will cause difficulty in dispersing the first catalyst slurry; if the alcohol content is too high, it will easily cause cracks in the first catalytic layer during coating, affecting the life of the membrane electrode.
[0025] As a more preferred embodiment of the method for preparing the membrane electrode cathode catalyst layer of the present invention, the alcohol in the first solvent is a low-boiling point alcohol with a boiling point of 64-100°C; the present invention uses low-boiling point alcohol mainly to make the solvent evaporate quickly and reduce the residue on the surface of the catalyst layer.
[0026] In the step S2 as a preferred embodiment of the method for preparing a membrane electrode cathode catalyst layer of the present invention, the second solvent and the first solvent can be the same solvent or different solvents.
[0027] As a preferred embodiment of the method for preparing the membrane electrode cathode catalyst layer of the present invention, the second solvent and the first solvent are a mixed solution of alcohol and water, and the alcohol is at least one of tert-butanol, n-propanol, isopropanol, ethanol, and methanol.
[0028] As a more preferred embodiment of the method for preparing the cathode catalyst layer of the membrane electrode according to the present invention, the content of alcohol in the second solvent is 5-30 wt %; more preferably 10-20 wt %.
[0029] As a preferred embodiment of the preparation method of the membrane electrode cathode catalyst layer of the present invention, in the step S2, the dispersion method is high-pressure homogeneous dispersion, and the dispersion pressure is 6000-20000psi; the inventors have found through a large number of experiments that in the present invention, the dispersion degree of the second catalyst slurry is the key factor in controlling the cracking of the second catalytic layer of the membrane electrode cathode catalyst layer. If the dispersion pressure of the second catalyst slurry is too low, the second catalyst slurry is not sufficiently dispersed, the second catalytic layer has a large roughness, but the catalytic layer is not easy to crack; if the dispersion pressure of the second catalyst slurry is too high, it will cause extremely large cracks in the second catalytic layer, resulting in discontinuity in proton conduction and electron conduction, affecting the performance of the membrane electrode.
[0030] In the step S3 as a preferred embodiment of the method for preparing the cathode catalyst layer of the membrane electrode according to the present invention, the coating method includes at least one of ultrasonic spraying, electrostatic spraying, blade coating, slit coating and screen printing.
[0031] As a preferred embodiment of the method for preparing the membrane electrode cathode catalyst layer of the present invention, the coating method is slit coating.
[0032] In a third aspect, the present invention provides a membrane electrode, wherein the membrane electrode comprises the membrane electrode cathode catalyst layer.
[0033] As a preferred embodiment of the membrane electrode of the present invention, the structure of the membrane electrode is an anode catalyst layer, a proton exchange membrane, and a cathode catalyst layer in sequence.
[0034] In a fourth aspect, the present invention provides a fuel cell, wherein the fuel cell comprises the membrane electrode as described in the third aspect.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The present invention uses a medium-long branched ionomer with a side chain carbon number of 3-7 and an EW of 700-1100 as the ionomer of the first catalytic layer, which can prevent the first catalytic layer from cracking and falling off after the solvent of the slurry penetrates into the first catalytic layer during the coating of the second catalyst slurry on the surface of the first catalytic layer, thereby ensuring the integrity of the first catalytic layer;
[0037] (2) By controlling the dispersion pressure of the second catalyst slurry during dispersion, the cracking degree of the cathode catalyst layer of the membrane electrode is controlled, which effectively increases the mass transfer channel and the reaction area. At the same time, the cracks do not penetrate the entire catalyst layer, thereby improving the performance of the membrane electrode and not causing accelerated degradation of the local proton exchange membrane during fuel cell operation, thereby affecting the life of the membrane electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1The scanning electron microscope images of the second catalytic layer of Example 1, Example 3, Example 4, Comparative Example 1, Comparative Example 2, and Comparative Example 6 of the present invention;
[0039] Figure 2 The scanning electron microscope images of the cross-sections of the membrane electrode described in Example 1, Example 3, Example 4, and Comparative Example 6 of the present invention;
[0040] Figure 3 This is a picture of the surface coating of the membrane electrode cathode catalyst layer described in Example 1, Comparative Example 3, Comparative Example 4, and Comparative Example 5 of the present invention;
[0041] Figure 4 It is a schematic diagram of the structure of the membrane electrode of the present invention. DETAILED DESCRIPTION
[0042] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0043] Example 1
[0044] This embodiment provides a membrane electrode cathode catalyst layer, and the preparation method of the membrane electrode cathode catalyst layer is as follows:
[0045] S1. Weigh 5.1 g of Tec10E50E 50 wt% Pt / C catalyst (the oxygen content of the catalyst is 12.0 wt%) produced by Tanaka Precious Metals (TKK) of Japan, 12.8 g of perfluorosulfonic acid resin dispersion of 20 wt% Nation D2020 (EW=893-970, long-chain branched resin, the number of carbon atoms in the side chain is 5), 7.2 g of ethanol, and 39.0 g of ultrapure water; slowly add the Pt / C catalyst to the water in a stirring state, stir for 5 min, then add the perfluorosulfonic acid resin dispersion and stir for 2 min, then add ethanol and continue stirring for 2 min to complete the pre-dispersion of the slurry; disperse the slurry by a Beads mill disperser, the speed of the disperser is 3000 rpm, the dispersion time is 30 min, then collect the dispersed catalyst slurry for degassing treatment to obtain the first catalyst slurry;
[0046] S2. Weigh 5.1 g of Tec10E50E-HT 50 wt% Pt / C catalyst (catalyst oxygen content is 4.8 wt%) produced by Tanaka Precious Metals (TKK) of Japan, 8 g of IC154 perfluorosulfonic acid resin dispersion, 7.2 g of ethanol, and 39.0 g of ultrapure water; slowly add the Pt / C catalyst into the stirred water, stir for 5 min, then add the perfluorosulfonic acid resin dispersion and stir for 2 min, then add ethanol and continue stirring for 2 min to complete the pre-dispersion of the slurry; disperse the slurry through a high-pressure homogenizer, the dispersion pressure is 20000 psi, the dispersion times are 2 times, then collect the dispersed catalyst slurry for degassing treatment to obtain a second catalyst slurry;
[0047] S3, the first catalyst slurry is coated on one side of the proton exchange membrane by a slit coating method, and dried at 80°C to obtain a semi-CCM containing the first cathode catalyst layer, the Pt loading of the first catalyst layer is 0.1 mg / cm 2 , thickness is 3.0μm;
[0048] The second catalyst slurry was coated on the first catalyst layer by slit coating method and dried at 80°C to obtain the second catalyst layer. The Pt loading of the second catalyst layer was 0.15 mg / cm 2 , with a thickness of 4.5 μm; after drying, the membrane electrode cathode catalyst layer is obtained.
[0049] Example 2
[0050] The only difference between the preparation method of the membrane electrode cathode catalyst layer described in this embodiment and that described in Embodiment 1 is that in the step S1, the first ionomer is 12.8 g of 20 wt% EW800 (EW≈800, long-chain branched resin, with 4 side chain carbon atoms) perfluorosulfonic acid resin dispersion produced by 3M Company; the remaining steps are consistent with Embodiment 1.
[0051] Example 3
[0052] The only difference between the preparation method of the membrane electrode cathode catalyst layer described in this embodiment and that described in Embodiment 1 is that in step S2, the dispersion pressure is 10000 psi; the remaining steps are consistent with those in Embodiment 1.
[0053] Example 4
[0054] The only difference between the preparation method of the membrane electrode cathode catalyst layer described in this embodiment and that described in Embodiment 1 is that in step S2, the dispersion pressure is 8000 psi; the remaining steps are consistent with those in Embodiment 1.
[0055] Example 5
[0056] The only difference between the preparation method of the membrane electrode cathode catalyst layer described in this embodiment and that described in Embodiment 1 is that in step S2, the dispersion pressure is 6000 psi; the remaining steps are consistent with those in Embodiment 1.
[0057] Example 6
[0058] The only difference between the preparation method of the membrane electrode cathode catalyst layer described in this embodiment and that described in Embodiment 1 is that in step S1, the first ionomer is 12.8 g of a 20 wt% perfluorosulfonic acid resin dispersion of Nafion D2021 (EW=970-1052, long-chain branched resin, with 5 side chain carbon atoms); the remaining steps are consistent with those in Embodiment 1.
[0059] Example 7
[0060] The only difference between the preparation method of the membrane electrode cathode catalyst layer described in this embodiment and that described in Embodiment 1 is that in step S1, the first ionomer is 12.8 g of a 20 wt% Dongyue EW910 (EW≈910, long-chain branched resin, with 5 side chain carbon atoms) perfluorosulfonic acid resin dispersion; the remaining steps are consistent with Embodiment 1.
[0061] Example 8
[0062] The only difference between the preparation method of the membrane electrode cathode catalyst layer described in this embodiment and that described in Embodiment 1 is that in step S1, the first ionomer is 12.8 g of a perfluorosulfonic acid resin dispersion of 20 wt% IC100 (EW≈910, long-chain branched resin, with 5 side chain carbon atoms); the remaining steps are consistent with those of Embodiment 1.
[0063] Example 9
[0064] The difference between the preparation method of the membrane electrode cathode catalyst layer described in this embodiment and the embodiment 1 is that: in the steps S1 and S2, a 70wt% Pt / C catalyst (Hispec13100, JM) is used, and in the step S3, the first catalyst slurry is coated on one side of the proton exchange membrane by a slit coating method, and the Pt loading of the first catalyst layer is 0.05mg / cm 2 , thickness is 0.5 μm;
[0065] The second catalyst slurry was coated on the first catalyst layer by slit coating method and dried at 80°C to obtain the second catalyst layer. The Pt loading of the second catalyst layer was 0.05 mg / cm 2 , with a thickness of ~0.5μm; after drying, the membrane electrode cathode catalyst layer is obtained; the remaining steps are consistent with Example 1.
[0066] Example 10
[0067] The difference between the preparation method of the membrane electrode cathode catalyst layer described in this embodiment and the embodiment 1 is that: in the step S1, a 30wt% Pt / C catalyst (TEC10EA30e, TKK) is used, and in the step S3, the first catalyst slurry is coated on one side of the proton exchange membrane by a slit coating method, and the Pt loading of the first catalyst layer is 0.3mg / cm 2 , thickness is 15 μm;
[0068] The second catalyst slurry was coated on the first catalyst layer by slit coating method and dried at 80°C to obtain the second catalyst layer. The Pt loading of the second catalyst layer was 0.3 mg / cm 2 , with a thickness of 10 μm; after drying, the membrane electrode cathode catalyst layer is obtained; the remaining steps are consistent with Example 1.
[0069] Comparative Example 1
[0070] The difference between the preparation method of the membrane electrode cathode catalyst layer described in this comparative example and that described in Example 1 is that in step S2, the dispersion pressure is <6000psi; the remaining steps are consistent with those in Example 1.
[0071] Comparative Example 2
[0072] The difference between the preparation method of the membrane electrode cathode catalyst layer described in this comparative example and that described in Example 1 is that in step S2, the dispersion pressure is >20000psi; the remaining steps are consistent with those in Example 1.
[0073] Comparative Example 3
[0074] The only difference between the preparation method of the membrane electrode cathode catalyst layer described in this comparative example and Example 1 is that in step S1, the first ionomer is 12.8 g of a 20wt% perfluorosulfonic acid resin dispersion of Solvay D72 (EW=~720, short-chain branched resin, with 2 side chain carbon atoms); the remaining steps are consistent with Example 1.
[0075] Comparative Example 4
[0076] The difference between the preparation method of the membrane electrode cathode catalyst layer described in this comparative example and the method described in Example 1 is that in step S3, the second catalyst slurry is coated on the first catalyst layer by a slit coating method and dried at 80°C to obtain the second catalyst layer. The Pt loading of the second catalyst layer is 0.03 mg / cm 2 , with a thickness of 1.0 μm; after drying, a membrane electrode cathode catalyst layer is obtained; the remaining steps are consistent with Example 1.
[0077] Comparative Example 5
[0078] The difference between the preparation method of the membrane electrode cathode catalyst layer described in this comparative example and the method described in Example 1 is that in step S3, the first catalyst slurry is coated on one side of the proton exchange membrane by a slit coating method, and the Pt loading of the first catalyst layer is 0.45 mg / cm 2 , thickness is 15μm; the second catalytic layer is not coated.
[0079] Comparative Example 6
[0080] The only difference between this comparative example and the method for preparing the membrane electrode cathode catalyst layer described in Example 1 is that in step S2, the slurry is dispersed by a Beads mill disperser, the speed of the disperser is 3000 rpm, the dispersion time is 30 min, and then the dispersed catalyst slurry is collected for degassing to obtain a second catalyst slurry; the remaining steps are consistent with Example 1.
[0081] Performance Test:
[0082] 1. The cathode catalyst layer obtained in each embodiment and comparative example and the samples after being made into membrane electrode were characterized for catalyst layer cracks. The results are as follows: Figure 1 , 2 shown.
[0083] Figure 1 , 2 The results show that in Examples 1, 3, and 4, the dispersion pressure of the second catalytic layer gradually decreases, the degree of cracking of the catalytic layer gradually decreases, the cracking of the catalytic layer is only in the surface layer of the catalytic layer, and the bottom layer remains intact; Example 6 disperses the second catalytic layer in the same way as the first catalytic layer, and the second catalytic layer presents a non-cracked surface morphology; in Example 1, if the dispersion pressure of the second catalyst slurry is too low, the second catalyst slurry is not sufficiently dispersed, the second catalytic layer has a large roughness, and the catalytic layer is not easy to crack; in Example 2, if the dispersion pressure of the second catalyst slurry is too high, it will cause huge cracks in the second catalytic layer, making its adsorption force worse, affecting the performance of the membrane electrode cathode catalytic layer.
[0084] 2. The membrane electrode cathode catalyst layer coatings of Example 1, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were characterized. The results are as follows: Figure 3 shown.
[0085] Figure 3 It is shown that Comparative Example 3 uses a short-chain branched ionomer as the first ionomer. Since the short-chain branched ionomer has a large swelling rate, it is easy to undergo volume changes after contacting water or alcohol solvents. After coating the second catalytic layer, it is easy to cause local swelling of the first catalytic layer, leading to cracking of the entire coating, and the integrity of the first catalytic layer cannot be guaranteed.
[0086] In Comparative Example 4, the platinum loading of the second catalytic layer is low, the thickness is small, and the surface catalytic layer is unevenly coated.
[0087] Comparative Example 5 was not coated with the second catalytic layer, and the platinum loading of the first catalytic layer was too high, resulting in severe cracking of the coating.
[0088] Finally, it should be noted that the above embodiments are used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a membrane electrode cathode catalyst layer, characterized in that: The preparation method comprises the following steps: S1, mixing and dispersing a first catalyst, a first solvent and a first ionomer to obtain a first catalyst slurry; S2, mixing and dispersing the second catalyst, the second solvent and the second ionomer, wherein the dispersion method is high-pressure homogenization dispersion, the dispersion pressure is 20000 psi, and the dispersion times are 2 times; obtaining a second catalyst slurry; S3, applying the first catalyst slurry in step S1 and the second catalyst slurry in step S2 on a proton exchange membrane in sequence, and drying to obtain a membrane electrode cathode catalyst layer including a first catalyst layer and a second catalyst layer stacked in sequence; the first catalyst layer includes a first catalyst and a first ionomer, and the second catalyst layer includes a second catalyst and a second ionomer; The first ionomer has a side chain carbon atom number of 3-7 and an equivalent molecular weight of 700-1100; the first and second ionomers include perfluorosulfonic acid resin; The first catalyst is a Pt / C or Pt-M / C catalyst having a metal content of 10-80 wt%; the second catalyst is a Pt / C or Pt-M / C catalyst having a metal content of 10-80 wt%; wherein M is at least one of Co, Ni, Mn, Pd, Sn, Au, Ag, Ir, Ru, Cu, and Fe; The thickness of the first catalytic layer is 0.5-15 μm, and the platinum loading is 0.05-0.3 mg / cm 2 The thickness of the second catalytic layer is 0.5-10 μm, and the platinum loading is 0.05-0.3 mg / cm 2 ; The mass of the first ionomer is 20-45% of the mass of the first catalytic layer; the mass of the second ionomer is 20-45% of the mass of the second catalytic layer; The second solvent and the first solvent are a mixed solution of alcohol and water, and the content of alcohol in the second solvent is 20wt%; The second catalytic layer has cracks which do not penetrate the entire catalytic layer, and the first catalytic layer has no cracks.
2. The membrane electrode cathode catalyst layer prepared by the preparation method as claimed in claim 1.
3. A membrane electrode, characterized in that: The membrane electrode comprises the membrane electrode cathode catalyst layer as claimed in claim 2.
4. A fuel cell, characterized in that: The fuel cell comprises the membrane electrode according to claim 3.
Citation Information
Patent Citations
Fuel cell catalyst layer slurry capable of enhancing oxygen transfer as well as preparation method and application of fuel cell catalyst layer slurry
CN115295809A
Membrane electrode cathode catalyst layer and preparation method and application thereof
CN116154187A
Hydrogen-oxygen fuel cell catalyst layer with multi-component ionomer gradient distribution structure and preparation method of hydrogen-oxygen fuel cell catalyst layer
CN116979069A